Avaliação de marcadores inflamatórios e antígenos ABO em pacientes com diagnóstico de câncer de próstata - Mastella, Aline Klein (2008)
Prostate cancer (PC) is a disease in men and became the first cause of death by cancer in Brazil. The carcinogenesis is related to the presence of local inflammatory process and to the loss of blood group in neoplasic cells. The aim of the study was to assess the involvement of inflammatory process and the expression of A and B antigens in prostate cancer. Serological measure of prostatic specific antigen (PSA), reactive C protein (CRP) and ischemia modified albumin (IMA) was made in healthy, hyperplasic (BPH) and neoplasic prostate volunteers. PSA values increased when comparing healthy (1,13 ng/ml), BPH (18,69 ng/ml) and PC (134,68 ng/ml) patients. IMA showed to be over 0,400 ABSU just in BPH patients. Medium CRP concentrations did not exceed normal values (5 mg/l) in the studied groups. There was not a meaningful difference in the evaluation of PSA, CRP and IMA in relation to the ABO blood group of the patients. The carcinogenesis of prostate seemed to abolish the expression of A and B antigens in neoplasic cells. Inflammatory feature showed to be mild in the prostatic alterations and did not reach reference values. IMA acted as a marker of oxidative stress and patients with BPH demonstrated concentration above 0,400 ABSU. The diagnosis of BPH must be considered when IMA is being used as a marker of myocardial ischemia. The ABO blood group of the volunteers did not show difference in the analysis of PSA, CRP and IMA.